2021
DOI: 10.1371/journal.pone.0256088
|View full text |Cite
|
Sign up to set email alerts
|

Sadness regulation strategies and measurement: A scoping review

Abstract: Backgrounds Accurate measurement and suitable strategies facilitate people regulate their sadness in an effective manner. Regulating or mitigating negative emotions, particularly sadness, is crucial mainly because constant negative emotions may lead to psychological disorders, such as depression and anxiety. This paper presents an overview of sadness regulation strategies and related measurement. Method Upon adhering to five-step scoping review, this study combed through articles that looked into sadness reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Despite an increasing effort to unite coping and emotion regulation from a conceptual standpoint (Compas et al, 2014; Stanisławski, 2019; Troy et al, 2023), virtually all reviews of their self-reported measures have been led in parallel, which limits the appreciation of similarities and distinctions. Among those reviewed, most validated scales focused on strategies typically used, as a disposition (trait like), by nonclinical adult samples (Greenaway et al, 2014; Kato, 2015; Núñez et al, 2022; Penley et al, 2002; Zaid et al, 2021). Besides, a growing field is emerging on intensive longitudinal assessment methodologies that permit a better consideration of the contexts in which such strategies are implemented (i.e., in-the-moment coping/emotion regulation; state like), with most reviews targeting emotion regulation (Boemo et al, 2022; Schatten et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an increasing effort to unite coping and emotion regulation from a conceptual standpoint (Compas et al, 2014; Stanisławski, 2019; Troy et al, 2023), virtually all reviews of their self-reported measures have been led in parallel, which limits the appreciation of similarities and distinctions. Among those reviewed, most validated scales focused on strategies typically used, as a disposition (trait like), by nonclinical adult samples (Greenaway et al, 2014; Kato, 2015; Núñez et al, 2022; Penley et al, 2002; Zaid et al, 2021). Besides, a growing field is emerging on intensive longitudinal assessment methodologies that permit a better consideration of the contexts in which such strategies are implemented (i.e., in-the-moment coping/emotion regulation; state like), with most reviews targeting emotion regulation (Boemo et al, 2022; Schatten et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Relevant data from each retained article was then extracted (Stage 4). As done in prior reviews (Núñez et al, 2022; Zaid et al, 2021) and suggested elsewhere (Arksey & O’Malley, 2005; Peters et al, 2015), we coded the following elements for each coping and emotion regulation measure: name, year of publication, country of study completion, structure of the measure (e.g., construct evaluated, number of items, strategies covered, time frame, context, and response options), sample characteristics, and psychometric properties. As psychometric properties, we retained internal consistency for multi-item validated scales and intraclass correlations (ICC) for the intensive longitudinal assessments, as they were the ones available for most measures.…”
Section: Scoping Review Protocolmentioning
confidence: 99%
“…Feeling sad arises with a valued loss. Exploring feeling sad in different disciplines indicated that feeling sad arises from a valued loss (Bunkers, 2010;Draper, 1999;Freed & Mann, 2007;Garg, 2019;Garg & Lerner, 2013;Gunderson et al, 2021;Knowles & Langley, 2012;Lazarus, 1991;Levenson, 1999;Mouchet-Mages & Baylé, 2008;Nesse, 1990;Phillips, 2009;Rivers et al, 2006;Smith & Lazarus, 1993;Tahlier et al, 2013;Zaid et al, 2021). For instance, Garg (2019) emphasized the importance of feeling sad as the most experienced emotion among all negative emotions.…”
Section: Exploring With Pattern Preferencesmentioning
confidence: 99%
“…As a result, some systematic reviews have been conducted on instruments for measuring ER. In general, these approaches have assessed the measurement of strategies in rather specific age groups and contexts, such as individuals with autism spectrum disorder,38 women with breast cancer,31 children and adolescents with intellectual disabilities,39 children’s ER in a school setting40 or evaluating specific strategies for coping with emotional states such as sadness 41. While these reviews have addressed the most relevant instruments and methods used to measure ER, the emphasis has been more on the measurement format (eg, self-report, interviews, behavioural observation) than on the instrument’s quality or psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…While these reviews have addressed the most relevant instruments and methods used to measure ER, the emphasis has been more on the measurement format (eg, self-report, interviews, behavioural observation) than on the instrument’s quality or psychometric properties. Moreover, most studies have reported only basic indicators such as internal consistency indices used to provide a broad assessment of the measure’s validity and reliability 41…”
Section: Introductionmentioning
confidence: 99%